Evaluation of topical antifungal products in an in vitro onychomycosis model. Issue 5 (9th February 2016) - Sleven, Reindert; Lanckacker, Ellen; Delputte, Peter; Maes, Louis; Cos, Paul
Summary: Many topical commercial products are currently available for the treatment of onychomycosis. However, limited data are available concerning their antifungal activity. Using an in vitro onychomycosis model, the daily application of seven nail formulations was compared to the antifungal reference drug amorolfine (Loceryl ® ) and evaluated for inhibitory activity against Trichophyton mentagrophytes using an agar diffusion test. Of all commercial nail formulations, only Excilor ® and Nailner ® demonstrated inhibitory activity, which was much lower compared to the daily application of Loceryl ® . However, Excilor ® showed similar efficacy compared to the conventional weekly application of Loceryl ® . These results suggest a role for organic acids in the antifungal effect of Excilor ® (acetic acid, ethyl lactate) and Nailner ® (lactic acid, citric acid, ethyl lactate) as all tested formulations without organic acids were inactive.